A new plasmonic Pickering emulsion based SERS sensor for in situ reaction monitoring and kinetic study. Issue 4 (24th December 2015) - Ouyang, Lei; Li, Dingyi; Zhu, Lihua; Yang, Wenwen; Tang, Heqing
Abstract : β-CD modified plasmonic Pickering emulsions were synthesized for interfacial reaction monitoring as well as for kinetic study. Abstract : Surface enhanced Raman spectroscopy (SERS) is still rarely used in application for non-SERS active molecules and multi-phase reaction observation due to its limitations of a non-functional substrate and a single-phase based detection system. For the first time, herein we used HS-β-cyclodextrin (HS-CD) as both an emulsifier and a functional molecule to develop a new Pickering emulsion-based SERS sensing system. HS-CD modified Ag NPs were emulsified to assemble into Pickering emulsions with paraffin as an organic phase. The new assembled structure not only promoted the SERS performance of the sol-based substrate with dense hot spots, but also made it accessible for multiphase analysis and interfacial reaction monitoring. Two processes were in situ monitored and their kinetics has also been explored on the basis of the newly proposed substrate system. The first one was an off-line observation of the reaction of o -phenylenediamine (OPD) with NO2 − to form benzotriazole (BTA). The second one was the on-line monitoring of surface plasmonic resonance (SPR) catalytic oxidation of OPD, together with the clarification of the reaction mechanism. Such a plasmonic emulsion based SERS platform shows good prospects in both homogenous and multi-phase interface reaction monitoring and kinetic study.